Development of Forward Roll Learning Through Modification of The Games - Selvi Melianty; Abdul Sukur; Firmansyah Dlis; Desy Tya Maya Ningrum (Universitas PGRI Palembang, 2022)
The purpose of this research is to develop a forward roll learning media through modification of the front roll game, so that students can learn the material and technique of the front roll without feeling difficult and bored with the modification of the front roll game. The subjects of this study were seventh grade students of SMP Negeri 3 Palembang. This research method is the development and design of this research refers to the development model (research and development). Development research has ten steps, but in this study eight of the ten steps proposed by Bord and Gall were used. The research and development as well as the procedures carried out, resulted in a product in the form of learning media for the basic techniques of front scissor on floor gymnastics through game modifications, namely; (1) introduction, explaining what modification of the front roll game is and how to help the front and back roll., (2) the core, Showing the game modification video and how to help the front roll, (3) closing; displays the evaluation of objective questions regarding the forward roll. The results of this study are the development of learning media for front roll material in lantau gymnastics through game modifications for class VII SMP Negeri 3 Palembang.